Sub-centres and Urban Inequality: A study on Social Equity in the Barcelona Metropolitan Region - Jaume Masip Tresserra (European Regional Science Association (ERSA), 2013)
Much of the inequality literature has done a great deal of work to study national inequality. However, most people live in cities and their experience of inequality is shaped by their local and metropolitan environment. This fact implies that next to inequality in countries, local inequality is also important. In this context, this paper investigates the relationship that exists between the urban spatial structure (defined by means of CBD and sub-centres) and the causes and the consequences of urban inequality in cities. To do so, this research takes into account the Barcelona Metropolitan Region as study case. Hence, the aim of this work is to determine whether CBD (central business district) and in particularly sub-centres, exert an influence on urban inequality in order to define future polices that enhance social equity. What determines the degree of inequality across the municipalities of the Barcelona Metropolitan Region and, what are the factors behind the inequality growth across these municipalities?. The former question is addressed through using spatial econometric techniques that estimate if per capita income in 2008 is dependent on the past agglomeration economies that have emerged from CBD and sub-centres in 2001 correspondingly. Consequently, the latter point is also studied, through examining whether urbanization and localization economies that have emerged from CBD and sub-centres in the past, matters for the per capita income growth between 2001 and 2008. The results suggest that agglomeration economies that arise from CBD and sub-centres can explain the degree of income inequality and its growth as well. In addition, once is controlled for other conditions, the econometric models reveal that initial income inequality, population density, presence of human capital, land use balance, urban amenities and coast location are positively associated with per capita income as well as they predict its growth until 2008. Inversely, high level of elderly population is negatively significant correlated with per capita income and its growth. Therefore, planning a metropolitan area by taking into account sub-centres entail a remarkably improvement of its social performance.
Keywords: J30; J31; J39; R11; 330; URBAN STRUCTURE; URBAN INEQUALITY; POLYCENTRISM; SUB-CENTRES; SOCIAL EQUITY; INCOME PER CAPITA; METROPOLITAN AREAS